Proceedings of the Ocean Drilling Program, 148 Scientific Results 1996
DOI: 10.2973/odp.proc.sr.148.157.1996
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction in Oceanic Dikes, Hole 504B

Abstract: Porosity, cation-exchange capacity (CEC), and electrical conductivity have been measured on 28 doleritic minicores from Deep Sea Drilling Project (DSDP) and Ocean Drilling Program (ODP) Hole 504B (Legs 137, 140, and 148). Conductivity experiments were performed under five different saturating-fluid salinities, at room temperature and pressure, and with a twoelectrode conducting cell. At 4 kHz, the porosity is related to the "intrinsic" formation factor by an inverse power law similar to Archie's formula F = a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
5
9
0
Order By: Relevance
“…The second additive term in this last equation corresponds to the surface conductivity σ S . Equation 6 is also very close to the equation proposed by Revil et al (1996) (their equation 15) for watersaturated doleritic core samples from the oceanic crust. A simple generalization of the above expression to anisotropic media yields the following expression for the in-phase conductivity tensor…”
Section: The Isotropic Case and Its Generalizationsupporting
confidence: 80%
See 1 more Smart Citation
“…The second additive term in this last equation corresponds to the surface conductivity σ S . Equation 6 is also very close to the equation proposed by Revil et al (1996) (their equation 15) for watersaturated doleritic core samples from the oceanic crust. A simple generalization of the above expression to anisotropic media yields the following expression for the in-phase conductivity tensor…”
Section: The Isotropic Case and Its Generalizationsupporting
confidence: 80%
“…Tortuosity in this case can also be related to the aspect ratio of grains, as discussed in Mandelson and Cohen (1982). Other published experimental works have report very high tortuosities; for instance Revil et al (1996) reported tortuosities in the range of 2-46 for doleritic core samples. Zhang and Scherer (2012, their Table 6) have report electrical tortuosities in the range 2-118 for tight shales.…”
Section: Complex Conductivity Anisotropymentioning
confidence: 69%
“…Furthermore, model surface conductance is derived from measurements in NaCl solutions, and the influence of having a higher divalent cation content (40% of the total charge) in the boundary layers and/or interlayers is not known. An alternative explanation is to assume a high tortuosity for the network of conductive surfaces (Revil et al, 1996)…”
Section: Discussionmentioning
confidence: 99%
“…The results of Flóvenz et al (1985) for core samples from Icelandic geothermal wells, and of Pezard (1990) for basaltic cores from the Ocean Drilling Project support this conclusion. A thorough theoretical and experimental study on this subject has been undertaken by Revil et al (1996Revil et al ( , 2002 and Revil and Glover (1997).…”
Section: Electrical Conduction Mechanisms and Their Temperature Depenmentioning
confidence: 99%